Education, Marital Status and Social Culture on Adolescent Pregnancy and Pregnancy of Productive Age At Wairiang Helath Center, Lembata District, East Nusa Tenggara, Indonesia - Herlinda Perada Masan; Rize Budi Amalia; Azimatul Karimah (Journal of Community Medicine and Public Health Research, 2026)
Lembata Regency is a district that contributes to annual teenage pregnancy rates in East Nusa Tenggara Province, Indonesia. Adolescent pregnancy not only has a negative impact on the health of teenagers and their babies, but it also has socio-cultural and economic impacts, requiring cross-sector collaboration for immediate handling. This research aims to analyze educational factors, marital status, and socio-cultural influences on the incidence of adolescent pregnancy. Using a type of observational analytical research with a case-control approach. The sampling technique used was consecutive sampling, with a sample size of 64 primigravida pregnant women at the Wairiang Health Center. The ratio was 1:3, with the case group (adolescent primigravida) comprising 16 people and the control group (productive-age primigravida) comprising 48 people. The research instrument used was a questionnaire. Data analysis used the chi-square test. The results of the study show that factors that have a significant relationship with first pregnancy as a teenager are education (p=0.003), marital status at the time of first pregnancy (p=0.014), with an OR value of 6.067 (95% CI (1.526-24.122)), and socio-cultural role. Socio-cultural role (p=0.001), with an OR value of 14.576 (95% CI (3.508-60.570)). Education, marital status, and socio-cultural role were found to be risk factors for first pregnancy as a teenager. Other factors that contribute to this are age and the role of religion in determining the validity of a marriage under customs, religion, and law.